Climate warming could increase recruitment success in glacier foreland plants - Mondoni, A.; Pedrini, Simone; Bernareggi, G.; Rossi, G.; Abeli, T.; Probert, R.J.; Ghitti, M.; Bonomi, C.; Orsenigo, S. (OXFORD UNIV PRESS, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Annals of Botany Company. All rights reserved. •